Laboratory-acquired infections with Brucella bacteria in China - Langui Song; Jiangmei Gao; Zhongdao Wu (Biosafety and Health, 2021)
Brucellosis is an important zoonotic infectious disease and is an important public health problem that causes serious economic consequences to the livestock industry. Brucella spp. comprise one of the most common pathogens causing laboratory-acquired infections (LAIs) and are becoming an increasingly important biosafety issue. To understand the significance of Brucella LAIs in China, related papers were search based on three Chinese databases (CNKI, Wanfang, and VIP), as well as PubMed. After assessment, 37 total cases were evaluated, including 27 students, seven laboratory technicians (one pregnant), two housekeeping staff, and one instructor. The age, sex, incubation period, pathogen detection results, and potential routes of infections were collected and analyzed. All LAIs occurred due to improper operations, inadequate biosafety training, and substandard laboratory safety conditions. Therefore, it is urgent to establish a comprehensive and systematic biosafety prevention/control system in laboratories to protect staff members from accidental exposures and LAIs; further, possible risks and control measures for the management of such infections were proposed.